THE EFFECT OF GREEN ACCOUNTING AND MATERIAL FLOW COST ACCOUNTING ON CORPORATE SUSTAINABILITY: THE MODERATING ROLE OF GOOD CORPORATE GOVERNANCE - Aqdiah; Suripto; Ani Kusumaningsih (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to analyze the influence of green accounting and material flow cost accounting (MFCA) on corporate sustainability with good corporate governance (GCG) as a moderating variable. The research population includes 43 textile and garment manufacturing companies listed on the Indonesia Stock Exchange, Malaysia Stock Exchange, and Singapore Exchange from 2021 to 2023. The research method employs panel data regression analysis with a fixed effect model approach. The results indicate that green accounting does not significantly affect corporate sustainability. MFCA in production flow shows a significant negative effect, while MFCA in production costs and production output show no significant effects. GCG strengthens the effect of MFCA production output on sustainability, but weakens the effect of MFCA production flow, and does not moderate the relationship between green accounting and sustainability. These findings indicate that the implementation of environmental accounting has not been optimal in supporting corporate sustainability, and the role of corporate governance varies depending on the dimensions of environmental accounting practices implemented.